Pengaruh Konformitas Teman Sebaya dan Money Availability Terhadap Impulse Buying Mahasiswa Melalui Self Control Sebagai Variabel Intervening - Saputra, Nurjanah Dea; Hermawan, Yoni; Kurniawan, Kurniawan (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research is motivated by the problem of impulse buying behavior that occurs in students majoring in Economics Education at Siliwangi University Class of 2020-2022 in Tasikmalaya. The aim is to determine the effect of peer conformity and money availability on student impulse buying through self-control as an intervening variable. The method used is a quantitative approach with a survey method, with an explanatory research design, and the data collection technique uses data with a questionnaire (questionnaire). The population in this study were students majoring in Economic Education, Faculty of Teacher Training and Education, Siliwangi University, Class of 2020-2022 with a total of 364 people. The sample obtained for the 2020 batch amounted to 61 people, the 2021 batch amounted to 57 people and the 2022 batch amounted to 73 people, so the total sample was 191 people. Sampling in this study used probability sampling techniques, namely proportionate stratified random sampling techniques. The results showed that peer conformity and money availability each have a direct influence on self-control with a significance value (0.000 <0.05). Furthermore, peer conformity has no direct effect on impulse buying with a significance value (0.615> 0.05), while money availability has a direct effect on impulse buying with a significance value (0.000 < 0.05) Then other results were obtained that self control had an effect on impulse buying with a significance value (0.004 < 0.05). Based on the Path Analysis test, it shows that peer conformity affects impulse buying through self control and money availability affects impulse buying through self control.